PENGOPTIMALAN KOMPETENSI MAHASISWA JURUSAN BAHASA DAN SASTRA INDONESIA FBS UNNES DALAM MEMBUAT MEDIA PEMBELAJARAN BAHASA INDONESIA MENGGUNAKAN ELEMEN AUTHENTIC ASSESSMENT - Mulyani, Mimi (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M), Universitas Negeri Semarang, 2010)
The learning-media subject aims for students to have the competence of makinga variety of instructional media. In fact, the studentÃ¢â¬Å¸s competences in designing, creating, and displaying the instructional media are not maximized since the media made by students is often not discussed in the class. A comprehensive measurement of aspects of learning; covering aspects of the process, performance, and product; can be done using authentic assessment approaches. The results show that the contextual elements of authentic assessment approach can improve students competence in designing, creating, and displaying graphics media. It also change their attitudes and interests from negative to positive. it is suggested that lecturers discuss the studentsÃ¢â¬Å¸ project in the lecture. Unnes is expected to improve the facilities of learning media that can lead students to be more creative and innovative in creating instructional media. Keywords: competence, instructional media, elements of authentic assessment